Edrophonium challenge test for blepharospasm - Matsumoto, Shinichi; Murakami, Hisanaga; Koizumi, Hidetaka; Takahashi, Masatoshi; Izumi, Yuishin; Kaji, Ryuji (Frontiers in Neuroscience, 2016)
Background: Blepharospasm is typically diagnosed clinically by excluding any secondary diseases and neuropsychiatric disorders because specific tests for blepharospasm are currently unavailable. Since anticholinergic agents are used to improve the symptoms of dystonia, we hypothesized that edrophonium chloride, an acetylcholinesterase inhibitor, may make the symptoms of dystonia apparent. Therefore, we examined whether an edrophonium challenge test would be useful in the diagnosis of blepharospasm. Methods: We studied 10 patients with blepharospasm and 10 with hemifacial spasms (as disease controls). We administered edrophonium and saline in this crossover study. Before and after the injection, we recorded the clinical signs using a video camera to assess the objective symptoms every 2 min. Ten minutes after the isotonic sodium chloride and edrophonium injections, the patients evaluated their subjective signs using a visual analog scale. The objective signs on the video recordings were scored by specialists who were blind to the treatment. Results: The subjective and objective signs of the patients with blepharospasm were amplified by edrophonium. In contrast, in patients with hemifacial spasms, the signs were not changed by the edrophonium challenge test. Conclusions: The edrophonium challenge test may be used to diagnose blepharospasm.